The emergence of azithromycin-resistant Salmonella Typhi in Nepal - Duy, PT; Dongol, S; Giri, A; Nguyen To, NT; Dan Thanh, HN; Nhu Quynh, NP; Duc Trung, P; Thwaites, GE; Basnyat, B; Baker, S; Rabaa, MA; Karkey, A (Oxford University Press, 2020)
Background Typhoid fever remains a significant cause of morbidity and mortality in Asia and Africa. The emergence of azithromycin resistance in South Asia is concerning, as azithromycin is one of the last effective oral drugs for treating typhoid.